A Simple Approach for the Synthesis of Thio-, Dithio- and Selenothiocarbamate-Tethered Peptidomimetics - Lalithamba, H. S.; Vishwanatha, T. M.; Reddy, M. Samarasimha; Sureshbabu, Vommina V. (Synlett, 2012)
A simple and efficient method is described for the synthesis of thio-, dithio- and selenothiocarbamate-linked peptidomimetics. The nucleophilic addition of enantiopure Nα-protected amino alkyl thiols to isocyanates, isothiocyanates or isoselenocyanates obtained from amino acid esters proceeds smoothly in the presence of catalytic amount of DMAP. The protocol was further extended for the synthesis of N,N′-orthogonally protected thio-, dithio- and selenothiocarbamate-linked peptidomimetics. The reaction is mild, free from racemization, and the products were obtained in good yield.
Keywords: peptidomimetics; isocyanates; isothiocyanates and isoselenocyanates; amino alkyl thiols; thiocarbamates; dithiocarbamates; selenothiocarbamates